A Comparative Study of E-Books and Printed Books on Academic Performance: Perception from the University Students - Saiju, Nisha; Tamang, Nisha; Tamang, Pramit; Bastola, Piyush; Bhattarai, Preeti; Neupane, Dasarath (International Journal of Humanities, Education, and Social Sciences, 2025)
The rise of digital learning resources has led to ongoing debates about the effectiveness of e-books compared to printed books in academic performance. University students are increasingly using both formats, but their impact on learning outcomes remains a subject of interest. This study explores students’ perceptions of e-books and printed books and their influence on academic performance. A quantitative research approach was employed to examine the comparative impact of e-books and printed books on academic performance. A structured questionnaire was distributed both online and offline to collect primary data from 210 university students across Shanker Dev Campus, Pulchowk Engineering Campus, Saraswoti Multiple Campus, and KIST College. Demographic analysis revealed that 96.7% of participants were undergraduates, with a balanced gender distribution (54.5% female, 45.5% male). Descriptive statistics indicated that printed books received higher mean ratings compared to e-books, particularly in perceived academic utility. Correlation analysis showed a moderate positive relationship between e-book usage and academic performance (r = 0.406, p < 0.001) and between printed book usage and academic performance (r = 0.449, p < 0.001), suggesting that both formats contribute to learning outcomes, with printed books having a slightly stronger association. The study found that both e-books and printed books positively impact academic performance, with printed books demonstrating a marginally stronger correlation. While e-books offer convenience and accessibility, printed books remain preferred for deeper comprehension and retention. The findings highlight the need for a balanced approach in integrating digital and traditional learning materials to optimize academic success.